In Vivo and in Vitro Effects of Nebivolol on Penile Structures in Hypertensive Rats - Toblli, Jorge Eduardo (2006)
Background: Erectile dysfunction is associated with high blood pressure and antihypertensive treatment, especially diuretics and traditional β-blockers. Nevertheless, new β-blockers such as nebivolol present some differences with respect to the classic β-blockers. The aim of this study was to determine the functional and morphologic effects of nebivolol on penile structures in hypertensive rats. Methods: During a 6-month period, male spontaneously hypertensive rat (SHR) and Wistar-Kyoto (WKY) rats were studied. The groups were as follows: 1) untreated SHR (Untreated-SHR); 2) SHR given nebivolol 10 mg/kg/day (SHR+N); 3) SHR given amlodipine 3 mg/kg/day (SHR+AML); and 4) untreated WKY (untreated-WKY). Cavernous smooth muscle (CSM) and vascular smooth muscle (VSM) from cavernous arteries, as well as collagen type III (COL III) in cavernous tissue, were evaluated. Results: After 6 months, SHR groups given nebivolol and amlodipine showed similar reductions in blood pressure compared with untreated SHR. However, only SHR+N and control WKY showed significantly lower values of CSM (P < 01), VSM (P < 01), and COL III (P < 01) when compared with untreated SHR and SHR+AML. In addition SHR+N showed a higher endothelial nitric oxide synthase expression in sinusoidal endothelium compared with SHR, and SHR+AML (P < 01). In vitro studies revealed that SHR+N displayed a better relaxation response to acetylcholine than untreated-SHR and SHR+AML (P < 01). Conclusion: Nebivolol presented equivalent BP control compared with amlodipine. However, only nebivolol showed a significant better functional outcome with a protective role against structural changes in erectile tissue that are caused by arterial hypertension.